Atherosclerosis Susceptibility Loci Identified in an Extremely Atherosclerosis‐Resistant Mouse Strain. Issue 4 (12th August 2013) - Rowlan, Jessica S.; Li, Qiongzhen; Manichaikul, Ani; Wang, Qian; Matsumoto, Alan H.; Shi, Weibin
Abstract : Background: C3H/HeJ (C3H) mice are extremely resistant to atherosclerosis, especially males. To understand the underlying genetic basis, we performed quantitative trait locus (QTL) analysis on a male F2 (the second generation from an intercross between 2 inbred strains) cohort derived from an intercross between C3H and C57BL/6 (B6) apolipoprotein E–deficient ( Apoe −/− ) mice. Methods and Results: Two hundred forty‐six male F2 mice were started on a Western diet at 8 weeks of age and kept on the diet for 5 weeks. Atherosclerotic lesions in the aortic root and fasting plasma lipid levels were measured. One hundred thirty‐four microsatellite markers across the entire genome were genotyped. Four significant QTLs on chromosomes (Chr) 2, 4, 9, and 15 and 4 suggestive loci on Chr1, Chr4, and Chr7 were identified for atherosclerotic lesions. Unexpectedly, the C3H allele was associated with increased lesion formation for 2 of the 4 significant QTLs. Six loci for high‐density lipoprotein (HDL), 6 for non‐HDL cholesterol, and 3 for triglycerides were also identified. The QTL for atherosclerosis on Chr9 replicated Ath29, originally mapped in a female F2 cohort derived from B6 and C3H Apoe −/− mice. This locus coincided with a QTL for HDL, and there was a moderate, but statistically significant, correlation between atherosclerotic lesion sizes and plasma HDL cholesterol levels in F2 mice. Conclusions: These data indicate that most atherosclerosis susceptibility loci are distinct from those for plasma lipids except for the Chr9 locus, which exerts effect through interactions with HDL.